2019
DOI: 10.1101/805887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction errors indexed by the P3 track the updating of complex long-term memory schemas

Abstract: Schemas are higher-level knowledge structures that store an abstraction of multiple previous experiences. They allow us to retain a multitude of information, but without the cost of storing every detail. Schemas are believed to be relatively stable, but occasionally have to be updated to remain useful in the face of changing environmental conditions. Once a schema is consolidated, schema updating has been proposed to be the result of a prediction error (PE) based learning mechanism, similar to the updating of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Consistent with our behavioral results, we found that self-congruent and selfincongruent feedback elicited distinct electrophysiological signatures suggesting a rapid discrimination between congruent and incongruent information. Our findings are consistent with ERP literature suggesting that schema-incongruent information triggers rapid electrophysiological responses (Höltje et al, 2019;Richter, 2020).These responses are postulated to reflect a mismatch between incoming information and activated schemas, triggering error signals that result in the updating of mental representations. In contrast, our findings suggested that self-incongruent information did not update participants' selfrepresentations.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our behavioral results, we found that self-congruent and selfincongruent feedback elicited distinct electrophysiological signatures suggesting a rapid discrimination between congruent and incongruent information. Our findings are consistent with ERP literature suggesting that schema-incongruent information triggers rapid electrophysiological responses (Höltje et al, 2019;Richter, 2020).These responses are postulated to reflect a mismatch between incoming information and activated schemas, triggering error signals that result in the updating of mental representations. In contrast, our findings suggested that self-incongruent information did not update participants' selfrepresentations.…”
Section: Discussionsupporting
confidence: 91%
“…The combination of latency, localization, and behavior in JC3 provides evidence that this component shares similarities with the characteristics of the late positive component (LPC; sometimes also referred to as the P300b). The LPC has been linked to post hoc memory schema updates, in which unexpected information either triggers greater long-term memory retrieval processes than expected information already stored in working memory (Olichney et al, 2000) or requires greater reliance on updates to an existing memory scheme (DeLong et al, 2014;Richter, 2019), resulting in a larger LPC amplitude. This effect is dependent on the ease of this process, and so individuals with more automated memory and language processes would be expected to have lower jICA loadings, as is the case in our findings.…”
Section: Discussionmentioning
confidence: 99%
“…As with behavioral experiments, clinicians administering imagery rescripting have not routinely incorporated intentional rehearsal into the postrescripting homework assignments that patients are instructed to complete in the week following interventions, although we propose that doing so could enhance treatment benefits in the manner detailed above. Indeed, basic experimental studies have shown that schema updating is strengthened in memory in accordance with the time dedicated to the consolidation of schema-inconsistent information (Korkki et al, 2021;Richter, 2020;Richter et al, 2019). Thus, after the acute administration of simulation-based interventions, clinicians should work with patients to deepen their processing of schemaincongruent information through intentional withinand between-sessions practice designed to enhance memory consolidation of new material.…”
Section: Eventmentioning
confidence: 99%